Computer experiments on the study of the binary star system - Мукушев , Б. (BULLETIN OF THE L.N. GUMILYOV EURASIAN NATIONAL UNIVERSITY. PHYSICS. ASTRONOMY SERIES, 2022)
The article presents the results of computer (computational) experiments. There has been carried out a theoretical analysis of the dynamic parameters of this space system. The authors reveal essence of the concepts of reduced and effective mass. The authors present computer models of the potential of the gravitational field of the "double star" system and the lines of the potential level of this fieldbased on the computational experiment. The article describes mechanisms of existence of the "double star - planet" system. The stable and unstable structures of binary stars are considered. There have been studiedtwo types of assumed stable orbits: a) the first type involves the move.